Equilibrium, affinity, dissociation constants, IC5O: Facts and fantasies. (12th April 2019) - Barbet, Jacques; Huclier‐Markai, Sandrine
SUMMARY: The interaction between ligands and receptors is often described in terms of 50% inhibitory concentrations ( IC50 ). However, IC50 values do not accurately reflect the dissociation constants ( Kd ), and the domain of application and precision of proposed approximations for Kd estimation are unclear. The effect of affinity and of experimental conditions on the differences between IC50 and Kd has been assessed from exact mass action law calculations and from computer simulations. Competitions between [ 111 In]DTPA‐indium and a few metal‐DTPA complexes for binding to a specific antibody are discussed as a practical example. Exact calculations of competition assays have been implemented in Microsoft Excel and performed for a variety of concentrations of receptor, tracer, and competitor. The results are identical to those of software packages. IC50 is found larger than Kd by less than 20% only when tracer concentration is small compared with Kd and to the receptor concentration and when this receptor concentration is small compared with Kd . Otherwise, Kd and IC50 may be very different and approximations proposed in the literature to obtain Kd values from graphically derived IC50 are not acceptable as soon as the concentrations of tracer or of receptor approach Kd . Under most experimental conditions, IC50 values do not reflect Kd values. Using available software packages to determine and report Kd values would allow for more meaningful comparisons of results obtained under different experimental conditions.